Soft tissue necrosis in patients treated with transoral robotic surgery and postoperative radiotherapy: preliminary results. Issue 6 (December 2020) - Alterio, Daniela; Tagliabue, Marta; Muto, Matteo; Zorzi, Stefano; Volpe, Stefania; Gandini, Sara; Sibio, Daniela; Bayır, Ömer; Marvaso, Giulia; Ferrari, Annamaria; Bruschini, Roberto; Cossu Rocca, Maria; et al.
Objective: Postoperative radiotherapy (PORT) is indicated in almost two-thirds of patients treated with transoral robotic surgery (TORS) for head and neck tumors. The aim of this study was to quantify the toxicity profile of patients treated with PORT after TORS in oropharyngeal and supraglottic laryngeal cancer focusing on soft tissue necrosis (STN). Methods: We retrospectively reviewed 28 patients. Acute and late toxicity were examined. Incidence and severity of STN were recorded. Results: No patient experienced acute grade 3 skin or mucosal toxicity; 1 patient had grade 3 dysphagia. At 12 months, no evaluated patient required enteral nutrition and 2 patients had tracheostomy. STN occurred in 4 (14%) patients: 3 out of 4 (75%) patients with STN had diabetes, whereas 6 out of 13 (25%) patients without STN had diabetes ( p = 0.05). Conclusion: We found an acceptable toxicity profile of PORT performed after a TORS procedure. Diabetes mellitus might be a risk factor for STN.